Effect of muscle fatigue and physical activity level in motor control of the gait of young adults - Barbieri, Fabio Augusto [UNESP]; dos Santos, Paulo Cezar Rocha [UNESP]; Vitório, Rodrigo [UNESP]; van Dieën, Jaap H.; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2013)
The aim of this study was to analyze the effect of muscle fatigue in active and inactive young adults on the kinematic and kinetic parameters of normal gait and obstacle crossing. Twenty male subjects were divided into active (10) and inactive (10), based on self-reported physical activity. Participants performed three trials of two tasks (normal gait and obstacle crossing) before and after a fatigue protocol, consisting of repeated sit-to-stand transfers until the instructed pace could no longer be maintained. MANOVAs were used to compare dependent variables with the following factors: physical activity level, fatigue and task. The endurance time in the fatigue protocol was lower for the inactive group. Changes of gait parameters with fatigue, among which increased step width and increased stride speed were the most consistent, were independent of task and physical activity level. These findings indicate that the kinematic and kinetic parameters of gait are affected by muscle fatigue irrespective of the physical activity level of the subjects and type of gait. Inactive individuals used a slightly different strategy than active individuals when crossing an obstacle, independently of muscle fatigue. © 2013.
Keywords: Fatigue; Motor control; Obstacle; Physical activity; Walking